Thrombolysis in acute ST Elevation Myocardial Infarction: determination of door to needle time in a tertiary medical centre - Nik Azlan Nik Muhamad; Muhammad Yusri Y (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Door to needle (DTN) time for thrombolysis in the Emergency Department, Universiti Kebangsaan Malaysia Medical Centre (ED, UKMMC) is an indicator that can reduce mortality and morbidity of patients with ST Elevation Myocardial Infarction (STEMI). This study was conducted to determine factors that influence DTN time for acute ST Elevation Myocardial Infarction (STEMI) and whether it has achieved the recommended time of 30 minutes. A cross-sectional study was conducted among patients diagnosed with acute STEMI and thrombolysed in ED, UKMMC from June 2016 until March 2017. A data collection sheet was used to collect patient’s demographic data and clinical data which included time of arrival to ED, time of initial electrocardiogram (ECG), time of drug preparation and time of thrombolytic delivery to the patient. A total of 98 patients were included in this study. Majority of patients (77.6%) were thrombolysed more than 30 minutes following ED arrival. Mean DTN in ED, UKKMC was 59.28 + 36.01 minutes. The mean door to ECG time was 7.19 + 8.08 minutes and the mean drug preparation time was 9.86 + 7.51 minutes. Out of 76 (77.6%) patients that were thrombolysed after 30 minutes of ED arrival, 59.2% (n=45) were due to multiple disciplinary referral. Other factors were delay in performing initial ECG 19.8% (n=15), incorrect initial ECG interpretation 9.2% (n=7) and unavoidable need for prior resuscitation 9.2% (n=7). As a conclusion this study showed that there was an unacceptable delay in hospital thrombolysis for acute STEMI.